Development of a Knowledge Management Tool for the Ecotourism Community - Mat Nor, Mustafa Afanddi (2004)
Malaysian government is focusing more than ever on its ecotourism industry, which could soon become the nation's number-one source of foreign exchange. This industry is made up of hotels, restaurants, retail operations, transportation, travel agents, marketing organizations, tour operators and a host of other businesses, organizations and components. Therefore, Internet technology is widely used to support the operation of this industry.